Integrasi Agama dan Sains dalam Menghadapi Masalah Global - Ika Ika; Hamdan Yasir; Muhamad Miftahudin (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The increasing role of science and religion in human life challenges theoretical ideas that predict a decreasing impact of religion on recent societies. this relationship has led to ongoing debate about the correlation between science and religion. His research problem centers on understanding the current correlation between Islam and science. This research uses a qualitative descriptive research design, with a focus on library research and academic articles obtained from Google Scholar as the primary data source. These findings highlight the integral role of science and religion in human life, and emphasize the need for harmony. In general, science can be classified into 2, namely: natural sciences and humanities sciences. Both of these sciences are actually rooted in the Koran and Hadith. shows communicating the existence and attributes of Allah and everything that happens in the universe through his verses. The conclusion is that even though religious knowledge and science are not the same, this does not mean that the two things cannot be integrated, because both religious knowledge and science all come from Allah SWT.